Checklist of the Tree Flora of the Badami Forest (Bagalkot District) Karnataka, India - Bramhadande, Sneha P.; Dalavi Sharad, Jagdish V.; Kambale, S.; Gholave, Avinash R.; Yadav, Shrirang R. (Indian Forester, 2018)
Dry deciduous forests of Badami is one of the floristically rich forest of deccan peninsular region, which covers several habitats such as open grasslands, scrub forests, gravelly slopes, seasonal lakes, rocky plateaus and sandy plains which supports unique vegetation. Present work provides list of tree flora of Badami (Bagalkot district), Karnataka, which comprises 84 tree taxa belonging to 35 families and 68 genera. The families Fabaceae Lindl., Moraceae Gaudich., Rubiaceae Juss. are dominant among the arborescent flora. Acacia Mill. and Ficus L. are largest genera each having 4 tree taxa. Flowering and fruiting period, habitat and vegetation type is given for each tree taxa. A forest of Badami is very unique; however it is ignored by researchers and is constantly disturbed by local communities and tourists. These forests are the home of many insects, reptiles, birds and mammals and due to constant disturbances their existence is in trouble. Hence present work was undertaken to generate baseline data. Which become useful for conservation and sustainable utilization of extremely dry deciduous forest of Badami.